2008
DOI: 10.7205/milmed.173.10.1031
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Mental Health and Analysis of Relative Factors for New Chinese Recruits

Abstract: The mental health status of army recruits is closely related to their childhood environment, education level, parental relationship, and emotional intelligence. These factors should be considered by mental health workers, to help new army recruits adapt to the new environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
0
8
0
1
Order By: Relevance
“…The level of education has also been inconsistent in previous military studies 29-31. However, most studies on Korean male conscripts indicate that a lower level of education predicts a greater likelihood of psychological disturbances and psychiatric problems 27,28,32.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The level of education has also been inconsistent in previous military studies 29-31. However, most studies on Korean male conscripts indicate that a lower level of education predicts a greater likelihood of psychological disturbances and psychiatric problems 27,28,32.…”
Section: Discussionmentioning
confidence: 98%
“…This is important given that low SES has been identified as a risk factor for several mental disorders including personality disorder 23-26. However, this finding is inconsistent in military samples 27-29. These discrepancies may be attributable to the screening tests used during recruiting, thus leading to a decrease in the SES differences.…”
Section: Discussionmentioning
confidence: 99%
“…En el nuevo siglo, ha habido un aumento exponencial del número de estudios transculturales. La mayoría estos estudios internacionales y nacionales han indicado una relación alta y significativa entre IE y salud mental Bastian et al, 2005;Borges, Stratton, Wagner y Elam, 2009;Brown y Schutte, 2006;Brackett y Mayer, 2003;Ciarrochi et al, 2001;Ciarrochi et al, 2002;Day et al, 2005;Dawda y Hart, 2000;Donaldson-Feilder y Bond, 2004;Dulewicz et al, 2003;Fernández-Berrocal et al, 2004;Ghorbani et al, 2002;Hemmati et al, 2004 Saklofske et al, 2003;Schmidt y Andrykowski, 2004;Slaski y Cartwright, 2002;Tsaousis y Nikolaou, 2005;Yan et al, 2008).…”
Section: A) Ansiedad Y Depresiónunclassified
“…As major domestic disaster relief in China has increased in recent years, and international military peacekeeping operations, the mental health of military personnel has received intense attention from researchers in the fields of military medicine and psychology in China. [ 3 , 8 , 9 ] Previous studies showed that servicemen who are stationed perennially in the plateau experience psychological problems, [ 4 ] and the mental functions of servicemen who transferred from the plain to the plateau are also affected. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] Thereafter, it has been widely used in China to assess the mental health of people in various occupational groups. [ 3 , 9 , 20 ] In 2008, Yan et al [ 3 ] used the SCL-90 scale to assess comprehensively the mental health of new Chinese military recruits.…”
Section: Introductionmentioning
confidence: 99%